Lipoprotein(a) Modulates Carotid Atherosclerosis in Metabolic Syndrome - Cremonini, Anna Laura; Pasta, Andrea; Carbone, Federico; Visconti, Luca; Casula, Matteo; Elia, Edoardo; Bonaventura, Aldo; Liberale, Luca; Bertolotto, Maria; Artom, Nathan; Minetti, Silvia; Contini, Paola; et al. (Frontiers in Molecular Biosciences, 2022)
Background and aims: High Lipoprotein(a) [Lp(a)] is a well-established cardiovascular (CV) risk factor, but the effect of mildLy elevated Lp(a) on CV health are largely unknown. Our aim is to evaluate if Lp(a) is associated with the severity of carotid atherosclerosis (CA) in the specific subset of Metabolic Syndrome (MetS). Patients and methods: Subjects with diagnosed MetS and ultrasound-assessed CA were enrolled. Those patients were categorized according with the severity of CA (moderate vs. severe) and circulating levels of Lp(a) alongside with clinical, anthropometric and biochemical data were collected. Results: Sixty-five patients were finally included: twenty-five with moderate and forty with severe CA (all with asymptomatic disease). Intergroup comparison showed Lp(a) as the only significantly different variable (6 [2-12] mg/dL vs. 11.5 [6-29.5] mg/dL; p=0.018). Circulating levels of Lp(a) were also confirmed as the only variable independently associated with severity of CA at logistic regression analysis (OR 2.9 [95% CI 1.1 – 7.8]; p=0.040). ROC curve analysis for Lp(a) confirmed a serum level of 10 mg/dL as the best cut-off value (AUC 0.675 [95% CI 0.548-0.786]). Although sensitivity and specificity were suboptimal (69.0 % and 70.4%, respectively) – likely due to the small sample size – this result is in line with those previously reported in literature. Conclusions: Lp(a) is independently associated with severity of CA in the subgroup of MetS patients.